Binder for battery and application thereof

By using a binder that combines a polymer with a hydroxyl group, amino group or sulfhydryl group and a polymer containing ethylene oxide or isocyanate group, the problem of high cost of binder and insufficient mechanical performance in sulfide solid lithium batteries is solved, and a battery with high cycle stability and rate performance is achieved.

CN119709048APending Publication Date: 2025-03-28QINGDAO SAILIDA ENERGY STORAGE IND TECHNOLOGY RESEARCH INSTITUTE CO LTD

Patent Information

Application Number
CN202411728598.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The binder in existing sulfide solid lithium batteries has high cost, insufficient mechanical properties and poor stability, making it difficult to prepare high-performance positive electrode, negative electrode and sulfide electrolyte membranes at the same time.

Method used

The binder is used in combination with a polymer containing hydroxy, amino or sulfhydryl group and a polymer containing ethylene oxide or isocyanate group. At least one polymer is a liquid rubber polymer. The excellent mechanical properties of the electrode and electrolyte membrane are ensured through its good compatibility with sulfides and high mechanical strength.

Benefits of technology

It realizes the high cycle stability and rate performance of sulfide solid-state batteries, is suitable for roll-to-roll process preparation, has a wide electrochemical window, and is compatible with high voltage positive electrode and lithium alloy negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709048A_ABST
    Figure CN119709048A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of all-solid-state lithium batteries, and particularly relates to a binder for a battery as well as a preparation method and application of the binder. The binder for the battery comprises a polymer containing hydroxyl, amino or sulfydryl and a polymer containing oxirane group or isocyanate group, at least one of the polymer containing hydroxyl, amino or sulfydryl and the polymer containing oxirane group or isocyanate group is a liquid rubber polymer. The binder for the battery has the beneficial effects that the binder for the battery has good compatibility with sulfide, and the structure of the sulfide cannot be damaged; in addition, the binder for the battery has relatively high mechanical strength, relatively high elongation at break and relatively high tensile strength, can ensure that an electrode and a sulfide electrolyte membrane prepared from the binder have excellent mechanical properties, and is suitable for preparing a solid-state battery by a roll-to-roll process; the binding agent for the battery has a wide electrochemical window, and has good compatibility with a high-voltage positive electrode and a lithium alloy negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state lithium batteries, and in particular relates to a battery binder and application thereof. Background Art

[0002] Rechargeable lithium-ion batteries have been widely used in 3C electronic products, electric vehicles and other fields due to their advantages such as high specific energy, long life and no memory effect. However, given that commercial lithium batteries currently use volatile and flammable organic carbonate liquid electrolytes, which can easily lead to safety hazards such as fire and explosion, it is imperative to develop highly safe solid-state lithium batteries. As a technical route with important application potential, sulfide solid-state lithium batteries characterized by high ionic conductivity and flexible sulfide electrolyte membranes have received great attention from industry and academia.

[0003] At present, the positive electrode sheet, negative electrode sheet and sulfide electrolyte membrane in sulfide solid-state lithium batteries generally use polytetrafluoroethylene as a binder, which has the defects of high cost, insufficient mechanical properties and poor reduction stability. To solve this problem, the development of high-performance polymer binders has important application value. At present, some patents disclose the preparation and application of related binders. For example, patent CN202311759795.X discloses a sulfide solid electrolyte membrane, a preparation method thereof and an all-solid-state battery. By using a hydrogenated nitrile rubber / styrene butadiene rubber blended binder, the high flexibility and ionic conductivity of the sulfide electrolyte membrane can be achieved; patent CN202410154740.4 discloses a method for preparing solid-state battery electrodes and solid-state electrolyte membranes, involving the use of a hyperbranched functional polymer with low glass transition temperature, high temperature fluidity and ion conductivity as a binder, which can improve the cycle and rate performance of solid-state batteries compared to traditional polytetrafluoroethylene binders. However, most of the binders reported for sulfide solid-state batteries are difficult to prepare sulfide electrolyte membranes using dry processes due to poor chemical compatibility with sulfides, and the low mechanical modulus makes it difficult to inhibit the growth of lithium dendrites. On the other hand, due to insufficient mechanical properties, it is difficult to simultaneously prepare the positive electrode, negative electrode and sulfide electrolyte membrane of solid-state batteries and achieve excellent electrochemical performance of all-solid-state batteries. Therefore, the development of high-performance binders is an important technical approach to promote the commercial application of sulfide solid-state batteries and is of great significance. Summary of the invention

[0004] The present application provides a battery adhesive and application thereof, aiming to solve the problems of high cost, insufficient mechanical properties and poor stability of existing adhesives.

[0005] In a first aspect, the present application provides a binder for batteries, comprising a polymer containing a hydroxyl group, an amino group or a mercapto group and a polymer containing an ethylene oxide group or an isocyanate group; at least one of the polymer containing a hydroxyl group, an amino group or a mercapto group and the polymer containing an ethylene oxide group or an isocyanate group is a liquid rubber polymer.

[0006] The battery binder described in this application has good compatibility with sulfides and will not destroy the structure of sulfides; in addition, the battery binder described in this application has high mechanical strength, both high elongation at break and high tensile strength, which can ensure that the electrodes and sulfide electrolyte membranes prepared therefrom have excellent mechanical properties and are suitable for roll-to-roll process preparation of solid-state batteries. The battery binder described in this application has a wide electrochemical window and has good compatibility with high-voltage positive electrodes and lithium alloy negative electrodes.

[0007] According to some embodiments of the battery binder described in the present application, the polymer containing hydroxyl, amino or thiol includes one or more of a first type of liquid rubber, a first type of polyurethane, a first type of polyether and a first type of polyester containing hydroxyl, amino or thiol;

[0008] The number average molecular weight of the polymer containing hydroxyl, amino or thiol is 1000-10000 Da.

[0009] According to some embodiments of the battery binder described in the present application, the polymer containing an ethylene oxide group or an isocyanate group includes one or more of a second type of liquid rubber containing an ethylene oxide group or an isocyanate group, a second type of polyurethane, a second type of polyether, and a second type of polyester;

[0010] The number average molecular weight of the polymer containing ethylene oxide group or isocyanate group is 1000-10000 Da.

[0011] According to some embodiments of the battery binder described in the present application, the first type of liquid rubber includes one or more of nitrile rubber, styrene-butadiene rubber, polybutadiene rubber, polyurethane rubber, and polysulfide rubber containing terminal hydroxyl groups, amino groups, or mercapto groups.

[0012] According to some embodiments of the battery binder described in the present application, the second type of liquid rubber includes one or more of nitrile rubber, styrene-butadiene rubber, polybutadiene rubber and polyurethane rubber containing ethylene oxide groups or isocyanate groups.

[0013] According to some embodiments of the battery binder described in the present application, the mass ratio of the polymer containing a hydroxyl group, an amino group or a mercapto group to the polymer containing an ethylene oxide group or an isocyanate group is (5-95): (5-95).

[0014] The second aspect of the present application provides a use of the battery binder described in the first aspect of the present application in a battery.

[0015] The sulfide solid-state battery prepared by the battery binder described in the first aspect of the present application has high cycle stability and rate performance.

[0016] According to some embodiments of the application described in the present application, the battery is a sulfide solid-state lithium battery.

[0017] In a third aspect of the present application, a solid-state lithium battery is provided, comprising a positive electrode sheet, a negative electrode sheet, and a sulfide electrolyte membrane;

[0018] The room temperature ionic conductivity of the sulfide electrolyte membrane prepared by the binder described in the present application is above 1.5 mS / cm, and the prepared sulfide solid-state battery has high cycle stability and rate performance.

[0019] The positive electrode plate includes a positive electrode active material, a conductive agent, a sulfide electrolyte and the binder described in the first aspect of the present application.

[0020] According to some embodiments of the solid-state lithium battery described in the present application, the negative electrode plate includes a negative electrode active material, a conductive agent, a sulfide electrolyte and the binder described in the first aspect of the present application.

[0021] According to some embodiments of the solid-state lithium battery described in the present application, the sulfide electrolyte membrane includes a sulfide electrolyte and the binder described in the first aspect of the present application.

[0022] According to some embodiments of the solid-state lithium battery described in the present application, the positive electrode active material includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium iron sulfate and a ternary positive electrode material.

[0023] According to some embodiments of the solid-state lithium battery described in the present application, the negative electrode active material includes one or more of metallic lithium, lithium alloy, hard carbon, graphite, molybdenum disulfide, lithium titanate, graphene, silicon dioxide, antimony oxide and silicon monomer.

[0024] According to some embodiments of the solid-state lithium battery described in the present application, the conductive agent includes one or more of carbon nanotubes, carbon black, graphite, graphene, hard carbon and soft carbon.

[0025] According to some embodiments of the solid-state lithium battery described in the present application, the sulfide electrolyte includes Li 2 S.P. 2 S 5 , Li 3 PS 4 , Li 7 P 3 S11 , Li 6 PS 5 Cl, Li 9+x-y M x P 3-x S 12-y N y One or more of, wherein 0≤x≤2, 0≤y≤1, M includes one or more of Si, Ge, Sn, Pb, and N includes one or more of F, Cl, Br, and I.

[0026] According to some embodiments of the solid-state lithium battery described in the present application, the mass ratio of the positive electrode active material, the conductive agent, the sulfide electrolyte and the binder in the positive electrode plate is (80-98): (0.1-5): (1-15): (0.1-5).

[0027] According to some embodiments of the solid-state lithium battery described in the present application, the mass ratio of the negative electrode active material, the conductive agent, the sulfide electrolyte and the binder in the negative electrode plate is (85-100): (0-5): (0-15): (0-5).

[0028] According to some embodiments of the solid-state lithium battery described in the present application, the mass ratio of the sulfide electrolyte to the binder in the sulfide electrolyte membrane is (95-99): (1-5).

[0029] According to some embodiments of the solid-state lithium battery described in the present application, the sulfide electrolyte includes Li 2 S and P 2 S 5 The mixture of Li 2 S and P 2 S 5 The molar ratio is (70-80):(30-20).

[0030] According to some embodiments of the solid-state lithium battery described in the present application, the positive electrode sheet, the negative electrode sheet and the sulfide electrolyte membrane of the solid-state lithium battery are all prepared by a wet or dry process. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 These are the test results of the charge and discharge performance of the battery described in Example 1 of the present application.

[0032] Figure 2 These are the test results of the charge and discharge performance of the battery described in Example 1 of the present application. DETAILED DESCRIPTION

[0033] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0034] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0035] An embodiment of the present application provides a binder for a battery, comprising a polymer containing a hydroxyl group, an amino group or a mercapto group and a polymer containing an ethylene oxide group or an isocyanate group; at least one of the polymer containing a hydroxyl group, an amino group or a mercapto group and the polymer containing an ethylene oxide group or an isocyanate group is a liquid rubber polymer.

[0036] The battery binder described in this application has good compatibility with sulfides and will not destroy the structure of sulfides; in addition, the battery binder described in this application has high mechanical strength, both high elongation at break and high tensile strength, which can ensure that the electrodes and sulfide electrolyte membranes prepared therefrom have excellent mechanical properties and are suitable for roll-to-roll process preparation of solid-state batteries. The battery binder described in this application has a wide electrochemical window and has good compatibility with high-voltage positive electrodes and lithium alloy negative electrodes.

[0037] In some embodiments of the present application, the polymer containing hydroxyl, amino or thiol groups includes one or more of a first type of liquid rubber, a first type of polyurethane, a first type of polyether and a first type of polyester containing hydroxyl, amino or thiol groups;

[0038] The number average molecular weight of the polymer containing hydroxyl, amino or thiol is 1000-10000Da, such as 1000Da, 2000Da, 3000Da, 5000Da, 6000Da, 7000Da, 8000Da, 9000Da, 10000Da, etc. The number average molecular weight of the polymer is controlled within the range of 1000-10000Da, which can ensure that the reactant raw materials are in liquid state or can be melted within 100°C, and is suitable for dry preparation of electrodes.

[0039] In some embodiments of the present application, the polymer containing an ethylene oxide group or an isocyanate group includes one or more of a second type of liquid rubber containing an ethylene oxide group or an isocyanate group, a second type of polyurethane, a second type of polyether, and a second type of polyester.

[0040] The number average molecular weight of the polymer containing ethylene oxide or isocyanate group is 1000-10000Da, such as 1000Da, 2000Da, 3000Da, 5000Da, 6000Da, 7000Da, 8000Da, 9000Da, 10000Da, etc. The number average molecular weight of the polymer is controlled within the range of 1000-10000Da, which can ensure that the reactant raw material is in liquid state or can be melted within 100°C, and is suitable for dry preparation of electrodes.

[0041] In some embodiments of the present application, the first type of liquid rubber includes one or more of nitrile rubber, styrene-butadiene rubber, polybutadiene rubber, polyurethane rubber, and polysulfide rubber containing terminal hydroxyl groups, amino groups, or mercapto groups.

[0042] In some embodiments of the present application, the second type of liquid rubber includes one or more of nitrile rubber, styrene butadiene rubber, polybutadiene rubber and polyurethane rubber containing ethylene oxide groups or isocyanate groups.

[0043] In some embodiments of the present application, the mass ratio of the polymer containing hydroxyl, amino or thiol to the polymer containing oxirane or isocyanate is (5-95): (5-95), such as 5:95, 8:92, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, 90:10, 95:5, etc. The mass ratio is controlled within this range to ensure that the prepared binder has strong mechanical strength, high elongation at break and large tensile strength, and can ensure that the electrode and sulfide electrolyte membrane prepared therefrom have excellent mechanical properties, which are suitable for preparing solid-state batteries by roll-to-roll process.

[0044] In some embodiments of the present application, the battery binder is prepared by an in-situ nucleophilic reaction of a polymer containing a hydroxyl group, an amino group or a mercapto group with a polymer containing an oxirane group or an isocyanate group.

[0045] The embodiment of the present application also provides an application of the battery binder described in the first aspect of the present application in a battery, wherein the battery is a sulfide solid-state battery. The sulfide solid-state battery prepared by the battery binder described in the first aspect of the present application has high cycle stability and rate performance.

[0046] The embodiment of the present application also provides a solid-state lithium battery, including a positive electrode sheet, a negative electrode sheet, and a sulfide electrolyte membrane;

[0047] The positive electrode sheet comprises a positive electrode active material, a conductive agent, a sulfide electrolyte and the binder described in the first aspect of the present application;

[0048] The negative electrode plate comprises a negative electrode active material, a conductive agent, a sulfide electrolyte and the binder described in the first aspect of the present application;

[0049] The sulfide electrolyte membrane includes a sulfide electrolyte and the binder described in the first aspect of the present application.

[0050] The room temperature ionic conductivity of the sulfide electrolyte membrane prepared by the binder described in the present application is above 1.5 mS / cm, and the prepared sulfide solid-state battery has high cycle stability and rate performance.

[0051] In some embodiments of the present application, the positive electrode active material includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium iron sulfate and a ternary positive electrode material.

[0052] In some embodiments of the present application, the ternary positive electrode material includes NCM811 positive electrode material and / or NCM523 positive electrode material.

[0053] In some embodiments of the present application, the negative electrode active material includes one or more of metallic lithium, lithium alloy, hard carbon, graphite, molybdenum disulfide, lithium titanate, graphene, silicon dioxide, antimony oxide and silicon monomer.

[0054] In some embodiments of the present application, the conductive agent includes one or more of carbon nanotubes, carbon black, graphite, graphene, hard carbon and soft carbon.

[0055] In some embodiments of the present application, the sulfide electrolyte includes Li 2 S.P. 2 S 5 , Li 3 PS 4 , Li 7 P 3 S 11 , Li 6 PS 5 Cl, Li 9+x-y M x P 3-x S 12-y N y One or more of, wherein 0≤x≤2, 0≤y≤1, M includes one or more of Si, Ge, Sn, and Pb, and N includes one or more of F, Cl, Br, and I. The above sulfide electrolyte has high ionic conductivity at room temperature.

[0056] In some embodiments of the present application, the mass ratio of the positive electrode active material, the conductive agent, the sulfide electrolyte and the binder in the positive electrode plate is (80-98): (0.1-5): (1-15): (0.1-5).

[0057] In some embodiments of the present application, the mass ratio of the negative electrode active material, the conductive agent, the sulfide electrolyte and the binder in the negative electrode plate is (85-100): (0-5): (0-15): (0-5).

[0058] In some embodiments of the present application, the mass ratio of the sulfide electrolyte and the binder in the sulfide electrolyte membrane is (95-99): (1-5); selecting this mass ratio can ensure that the sulfide electrolyte membrane has both high ionic conductivity and excellent mechanical properties.

[0059] In some embodiments of the present application, the sulfide electrolyte includes Li 2 S and P 2 S 5 The mixture of Li 2 S and P 2 S 5 The molar ratio is (70-80):(30-20), for example 70:30, 75:25, 80:20, etc.

[0060] In some embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the sulfide electrolyte membrane of the solid-state lithium battery are prepared by a wet or dry process.

[0061] The technical solution of the present invention is described in detail below in conjunction with specific implementation cases and drawings.

[0062] In the present application, the performance test is carried out according to the following method:

[0063] 1. Electrolyte performance characterization

[0064] Ionic conductivity (σ): Platinum slurry is applied on both sides of the electrolyte. Through electrochemical impedance spectroscopy, according to the formula σ = L / AR, where L is the thickness of the electrolyte, A is the bottom area of ​​the electrolyte, and R is the measured resistance;

[0065] Electrochemical window: The electrolyte is sandwiched between a stainless steel sheet and a lithium sheet and placed in a 2032-type battery case. The electrochemical window is measured by linear voltammetry scanning using an electrochemical workstation, with a starting potential of 2.5 V, a maximum potential of 6 V, and a scan rate of 1 mV s -1 .

[0066] 2. Tensile strength and elongation at break of adhesive film

[0067] The adhesive was prepared into an adhesive film with a size of 20 um×2 cm×20 cm, and its stress-strain curve was tested using a universal tensile testing machine.

[0068] Breaking strength: The adhesive film is pressed into a size of 5×2.5×25mm 3 The shape is formed by hot pressing at 150-350℃. After cutting the sample with a depth of 2.5mm and a width of less than 0.2mm in the height direction, a three-point bending test is performed. According to the formula K IC =PS / BW (3 / 2) f(a / w), where P is the applied load on the specimen, B is the specimen width, W is the specimen height, S is the three-point bending span, a is the notch depth, and f(a / w) is the geometric shape factor of the specimen.

[0069] 3. Dry-process all-solid-state battery component preparation:

[0070] (1) Preparation of sulfide electrolyte membrane:

[0071] i. The binder is premixed in a twin-screw extruder for 10 minutes, and then the sulfide electrolyte particles are added into the twin-screw extruder according to a certain mass ratio, mixed and extruded, and hot-pressed into a sulfide electrolyte membrane with a thickness of 20 um under the conditions of 150° C. and 50 MPa.

[0072] (2) Preparation of positive electrode sheet:

[0073] i. The binder is premixed in a twin-screw extruder for 10 min, and then the positive electrode active material, the conductive additive, and the sulfide electrolyte particles are added to the twin-screw extruder in a certain mass ratio, mixed and extruded, and then hot-pressed into a positive electrode film of a certain thickness at 150° C. and 50 MPa;

[0074] ii. The dry positive electrode film prepared in the previous step is evenly coated on the aluminum foil by transfer, first heat treated at 60°C for 4h, then dried, rolled, punched and weighed in a vacuum oven at 120°C, and then continued to dry in a vacuum oven at 120°C to obtain a positive electrode sheet.

[0075] (3) Preparation of negative electrode sheet:

[0076] i. The binder is premixed in a twin-screw extruder for 10 minutes, and then the negative electrode active material (except lithium and its alloys), the conductive additive, and the sulfide electrolyte particles are added to the twin-screw extruder in a certain mass ratio, mixed and extruded, and then hot-pressed into a negative electrode film of a certain thickness at 150° C. and 50 MPa;

[0077] ii. The dry negative electrode film prepared in the previous step is evenly coated on the copper foil by transfer, first heat treated at 60°C for 4h, then dried, rolled, punched and weighed in a vacuum oven at 120°C, and then continued to dry in a vacuum oven at 120°C to obtain the negative electrode sheet.

[0078] 4. Wet-process all-solid-state battery component preparation:

[0079] (1) Preparation of sulfide electrolyte membrane:

[0080] i. The binder was dissolved in toluene solvent (solution concentration 0.1 g / mL), stirred at room temperature for 1 h, and then sulfide electrolyte particles were added and mixed to obtain a slurry;

[0081] ii. The slurry was coated onto a polytetrafluoroethylene substrate, and then dried at 60°C for 6 hours, and then dried at 120°C for 6 hours to obtain a sulfide electrolyte membrane. After further rolling and punching, the membrane was placed in a dew point drying room for use.

[0082] (2) Preparation of positive electrode sheet:

[0083] i. The binder was dissolved in toluene solvent (solution concentration 0.1 g / mL), stirred at room temperature for 1 h, and then the positive electrode active material, conductive additive, and sulfide electrolyte particles were added and mixed uniformly to obtain a slurry;

[0084] ii. The slurry was scraped onto aluminum foil, dried at 60°C for 6 hours, and then dried at 120°C for 6 hours to obtain a positive electrode film. After further rolling, punching, and weighing, the film was placed in a dew point drying room for use.

[0085] (3) Preparation of negative electrode sheet:

[0086] i. The binder is dissolved in toluene solvent (solution concentration 0.1 g / mL), stirred at room temperature for 1 h, and then the negative electrode active material (except lithium and its alloys), conductive additives, and sulfide electrolyte particles are added and mixed uniformly to obtain a slurry;

[0087] ii. The above slurry was scraped onto copper foil, dried at 60°C for 6 hours, and then dried at 120°C for 6 hours to obtain a negative electrode film. After further roller pressing, punching, and weighing, the film was placed in a dew point drying room for use.

[0088] Battery Assembly:

[0089] The negative electrode shell, negative electrode plate, electrolyte membrane, positive electrode plate and positive electrode shell were assembled in sequence, and then packaged into a battery, maintained at 50°C for 5 hours, and the battery performance was tested.

[0090] 5. Battery charge and discharge performance test:

[0091] The charge and discharge curves of all-solid-state secondary lithium batteries were tested using the LAND battery charge and discharge instrument.

[0092] Example 1

[0093] 0.1 g of terminal hydroxyl nitrile rubber (Mn=2000 Da) and 9.9 g of terminal isocyanate polybutadiene liquid rubber (Mn=3000 Da) were mixed in a mass ratio of 1:99 to prepare adhesive B1; the adhesive B1 film was tested using a universal tensile testing machine, and the elongation at break was 300%, and the tensile strength was 20 MPa.

[0094] Preparation of Li using binder B1 6 PS 5 Cl electrolyte membrane, NCM811 positive electrode and silicon negative electrode. Among them, the positive electrode plate is composed of NCM811 positive electrode material, carbon nanotubes, sulfide electrolyte, and the binder, with mass percentages of 80%, 5%, 10%, and 5% respectively; the negative electrode plate is composed of silicon monomer, carbon nanotubes, sulfide electrolyte, and the binder, with mass percentages of 80%, 5%, 10%, and 5% respectively; the sulfide electrolyte membrane is composed of sulfide electrolyte and the binder, with mass percentages of 95% and 5% respectively.

[0095] The sulfide electrolyte membrane prepared by the binder B1 has a thickness of 20 μm and a room temperature lithium ion conductivity of 3.3×10 - 3 Scm -1 , the initial decomposition voltage is 4.8V, and the breaking strength is 1.4MPa m -2 .

[0096] The sulfide electrolyte membrane prepared with the above binder B1, the NCM811 positive electrode sheet and the silicon negative electrode sheet were assembled into a full battery, and the charge and discharge performance test was carried out. The test results are as follows: Figure 1 shown.

[0097] from Figure 1 It can be seen that the capacity retention rate is 88% after 150 cycles at an operating voltage of 2.5-4.3V and 1.0C.

[0098] Comparative Example 1

[0099] The battery assembly method is the same as that of Example 1, except that Li 6 PS 5 The binder used in the Cl electrolyte membrane, NCM811 positive electrode and silicon negative electrode is polytetrafluoroethylene binder.

[0100] The room temperature lithium ion conductivity of the sulfide electrolyte membrane prepared in Comparative Example 1 is 2.8×10 -3 S cm -1, the initial decomposition voltage is 4.7V, and the breaking strength is 0.8MPa m -2 .

[0101] like Figure 1 As shown, the capacity retention rate of the battery prepared in Comparative Example 1 is only 57% after 148 cycles at an operating voltage of 2.5-4.3V and 1.0C.

[0102] Compared with Comparative Example 1, Example 1 exhibits better cycle performance because the binder used has higher ionic conductivity and better mechanical properties.

[0103] Example 2

[0104] Adhesive B2 was prepared by mixing 0.5 g amino-terminated polybutadiene rubber (Mn=1000 Da) and 9.5 g isocyanate-terminated polybutadiene liquid rubber (Mn=4000 Da) in a mass ratio of 5:95. The adhesive B2 film was tested using a universal tensile testing machine and the elongation at break was 300%, and the tensile strength was 20 MPa.

[0105] Li was prepared using binder B2. 6 PS 5 Cl electrolyte membrane, NCM811 positive electrode and silicon negative electrode. Among them, the positive electrode plate is composed of NCM811 positive electrode material, carbon nanotubes, sulfide electrolyte, and the binder, with mass percentages of 92%, 1%, 6%, and 1% respectively; the negative electrode plate is composed of silicon monomer, carbon nanotubes, sulfide electrolyte, and the binder, with mass percentages of 92%, 1%, 6%, and 1% respectively; the sulfide electrolyte membrane is composed of sulfide electrolyte and the binder, with mass percentages of 99% and 1% respectively.

[0106] The sulfide electrolyte membrane prepared by the binder B2 has a thickness of 20 μm and a room temperature lithium ion conductivity of 3.3×10 - 3 Scm -1 , the initial decomposition voltage is 4.8V, and the breaking strength is 1.4MPa m -2 .

[0107] Comparative Example 2

[0108] The battery assembly method is the same as that of Example 2, except that Li 6 PS 5 The binder used in the Cl electrolyte membrane, NCM811 positive electrode and silicon negative electrode is polytetrafluoroethylene binder.

[0109] The room temperature lithium ion conductivity of the sulfide electrolyte membrane prepared in Comparative Example 2 is 2.8×10 -3 S cm -1, the initial decomposition voltage is 4.7V, and the breaking strength is 0.8MPa m -2 .

[0110] The charge and discharge performance of the full battery assembled with the sulfide electrolyte membrane prepared with the above binder B2 and the binder polytetrafluoroethylene, the NCM811 positive electrode sheet and the silicon negative electrode sheet was tested. The test results are as follows: Figure 2 shown.

[0111] from Figure 2 It can be seen that the capacity retention rate is 89% after 130 cycles at an operating voltage of 2.5-4.3V and 1.0C, while the capacity retention rate of a full battery assembled with a sulfide electrolyte membrane prepared with a traditional polytetrafluoroethylene binder, an NCM811 positive electrode sheet and a silicon negative electrode sheet (the full battery is prepared by the preparation method described in the above embodiment) is only 36% after 130 cycles.

[0112] Compared with Comparative Example 2, Example 2 exhibits better cycle performance because the binder used has higher ionic conductivity and better mechanical properties.

[0113] Example 3

[0114] Adhesive B3 was prepared by mixing 2.0 g of mercapto-terminated polysulfide rubber (Mn=1500 Da) and 8.0 g of isocyanate-terminated polybutadiene liquid rubber (Mn=3000 Da) in a mass ratio of 1:4. The elongation at break of the adhesive B3 film tested by a universal tensile testing machine was 450%, and the tensile strength was 95 MPa.

[0115] Preparation of Li using binder B3 2 S and P 2 S 5 (Li 2 S and P 2 S 5 The electrolyte membrane, NCM523 positive electrode sheet and silicon oxide negative electrode sheet (mass ratio of 75:25) are prepared. The positive electrode sheet is composed of NCM523 positive electrode material, carbon black, sulfide electrolyte and the binder, with mass percentages of 87%, 5%, 6% and 2% respectively; the negative electrode sheet is composed of silicon oxide, carbon black, sulfide electrolyte and the binder, with mass percentages of 87%, 5%, 6% and 2% respectively; the sulfide electrolyte membrane is composed of sulfide electrolyte and the binder, with mass percentages of 97% and 3% respectively.

[0116] The sulfide electrolyte membrane prepared by the binder B3 has a thickness of 28 μm and a room temperature lithium ion conductivity of 3.6×10 - 3 Scm -1 , the initial decomposition voltage is 4.85V, and the breaking strength is 1.8MPa m-2 .

[0117] The sulfide electrolyte membrane prepared with the above binder B3, the NCM523 positive electrode sheet and the silicon oxide negative electrode sheet were assembled into a full battery and the charge and discharge performance was tested. After 300 cycles at an operating voltage of 2.5-4.4V and 1.0C, the capacity retention rate was 88%.

[0118] Comparative Example 3

[0119] The battery assembly method is the same as that of Example 3, except that the binder used in the electrolyte membrane, the NCM523 positive electrode plate and the silicon oxide negative electrode plate is a polytetrafluoroethylene binder.

[0120] Under the same testing conditions as in Example 3, the capacity retention rate of the full battery prepared in Comparative Example 3 after 100 cycles was only 75%.

[0121] Compared with Comparative Example 3, Example 3 exhibits better cycle performance because the binder used has higher ionic conductivity and better mechanical properties.

[0122] Example 4

[0123] Adhesive B4 was prepared by mixing 5.0 g of terminal hydroxyl polyurethane (prepared from polyethylene glycol and 1,5-naphthalene diisocyanate, Mn=4000Da) and 5.0 g of terminal ethylene oxide polybutadiene liquid rubber (Mn=6000Da) in a mass ratio of 1:1; the elongation at break of the adhesive B4 film tested by a universal tensile testing machine was 680%, and the tensile strength was 57 MPa.

[0124] Li was prepared using binder B4. 7 P 3 S 11 Electrolyte membrane, lithium cobalt oxide positive electrode sheet and silicon negative electrode sheet. The positive electrode sheet is composed of lithium cobalt oxide active material, carbon nanotubes, sulfide electrolyte and the binder, with the mass percentages of 81%, 2%, 15% and 2% respectively; the negative electrode sheet is composed of silicon monomer, carbon nanotubes, sulfide electrolyte and the binder, with the mass percentages of 81%, 2%, 15% and 2% respectively; the sulfide electrolyte membrane is composed of sulfide electrolyte and the binder, with the mass percentages of 98% and 2% respectively.

[0125] The sulfide electrolyte membrane prepared by the binder B4 has a thickness of 37 μm and a room temperature lithium ion conductivity of 2.9×10 - 3 Scm -1 , the initial decomposition voltage is 4.75V, and the breaking strength is 1.9MPa m -2 .

[0126] The sulfide electrolyte membrane prepared with the above binder B4, the lithium cobalt oxide positive electrode sheet and the silicon negative electrode sheet were assembled into a full battery and the charge and discharge performance was tested. The capacity retention rate was 97% after 200 cycles at an operating voltage of 2.5-4.5V and 1.0C.

[0127] Comparative Example 4

[0128] The battery assembly method is the same as that of Example 4, except that the binder used in the electrolyte membrane, the lithium cobalt oxide positive electrode plate and the silicon negative electrode plate is a polytetrafluoroethylene binder.

[0129] Under the same testing conditions as in Example 4, the capacity retention rate of the full battery prepared in Comparative Example 4 after 200 cycles was only 82%.

[0130] Compared with Comparative Example 4, Example 4 exhibits better cycle performance because the binder used has higher ionic conductivity and better mechanical properties.

[0131] Example 5

[0132] Adhesive B5 was prepared by mixing 9.0 g of amino-terminated polylactic acid ester (Mn=2500 Da) and 1.0 g of ethylene oxide-terminated polybutadiene liquid rubber (Mn=3500 Da) in a mass ratio of 9:1. The elongation at break of the adhesive B5 film tested by a universal tensile testing machine was 800%, and the tensile strength was 100 MPa.

[0133] Li was prepared using binder B5. 7 P 3 S 11 Electrolyte membrane, lithium cobalt oxide positive electrode sheet. The positive electrode sheet is composed of lithium cobalt oxide positive electrode active material, carbon nanotubes, sulfide electrolyte, and the binder, with mass percentages of 84%, 3%, 9%, and 4%, respectively; the sulfide electrolyte membrane is composed of sulfide electrolyte and the binder, with mass percentages of 96% and 4%, respectively.

[0134] The sulfide electrolyte membrane prepared by the binder B5 has a thickness of 28 μm and a room temperature lithium ion conductivity of 2.6×10 - 3 Scm -1 , the initial decomposition voltage is 4.8V, and the breaking strength is 3.5MPa m -2 .

[0135] Li prepared with binder B5 7 P 3 S 11 The electrolyte membrane, lithium cobalt oxide positive electrode sheet and lithium metal negative electrode sheet were assembled into a full battery and the charge and discharge performance was tested. After 400 cycles at an operating voltage of 2.5-4.4V and 1.0C, the capacity retention rate was 86%.

[0136] Comparative Example 5

[0137] The battery assembly method is the same as that of Example 5, except that the binder used in the electrolyte membrane and the lithium cobalt oxide positive electrode plate is a polytetrafluoroethylene binder.

[0138] Under the same testing conditions as in Example 5, the capacity retention rate of the full battery prepared in Comparative Example 5 after 400 cycles was only 71%.

[0139] Compared with Comparative Example 5, Example 5 exhibits better cycle performance because the binder used has higher ionic conductivity and better mechanical properties.

[0140] Example 6

[0141] Adhesive B6 was prepared by mixing 3.0 g of terminal mercapto polysulfide rubber (Mn=2000 Da) and 7.0 g of terminal isocyanate polybutadiene liquid rubber (Mn=3000 Da) in a mass ratio of 3:7. The elongation at break of the adhesive B6 film tested by a universal tensile testing machine was 570%, and the tensile strength was 45 MPa.

[0142] Preparation of Li using binder B6 7 P 3 S 11 Electrolyte membrane, lithium cobalt oxide positive electrode sheet and silicon negative electrode sheet. The positive electrode sheet is composed of lithium cobalt oxide positive electrode active material, carbon nanotubes, sulfide electrolyte and the binder, with the mass percentages of 85%, 2%, 10% and 3% respectively; the negative electrode sheet is composed of silicon monomer, carbon nanotubes, sulfide electrolyte and the binder, with the mass percentages of 85%, 2%, 10% and 3% respectively; the sulfide electrolyte membrane is composed of sulfide electrolyte and the binder, with the mass percentages of 95.5% and 4.5% respectively.

[0143] The sulfide electrolyte membrane prepared by the binder B6 has a thickness of 21 μm and a room temperature lithium ion conductivity of 3.45×10 -3 S cm -1 , the initial decomposition voltage is 4.8V, and the breaking strength is 3.8MPa m -2 .

[0144] The sulfide electrolyte membrane prepared with the above binder B6, the lithium cobalt oxide positive electrode and the silicon negative electrode were assembled into a full battery, and the charge and discharge performance was tested. After 300 cycles at an operating voltage of 2.5-4.4V and 0.5C, the capacity retention rate was 91%.

[0145] Comparative Example 6

[0146] The battery assembly method is the same as that of Example 6, except that the binder used in the electrolyte membrane, the lithium cobalt oxide positive electrode and the silicon negative electrode is a polytetrafluoroethylene binder.

[0147] Under the same testing conditions as in Example 6, the capacity retention rate of the full battery prepared in Comparative Example 6 after 300 cycles was only 82%.

[0148] Compared with Comparative Example 6, Example 6 exhibits better cycle performance because the binder used has higher ionic conductivity and better mechanical properties.

[0149] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A battery binder, characterized in that: The invention comprises a polymer containing hydroxyl, amino or mercapto group and a polymer containing ethylene oxide group or isocyanate group; at least one of the polymer containing hydroxyl, amino or mercapto group and the polymer containing ethylene oxide group or isocyanate group is a liquid rubber polymer.

2. The battery binder according to claim 1, characterized in that: The polymer containing hydroxyl, amino or mercapto groups includes one or more of the first type of liquid rubber, the first type of polyurethane, the first type of polyether and the first type of polyester containing hydroxyl, amino or mercapto groups; The number average molecular weight of the polymer containing hydroxyl, amino or thiol is 1000-10000Da; And / or, the polymer containing ethylene oxide group or isocyanate group includes one or more of the second type of liquid rubber, the second type of polyurethane, the second type of polyether and the second type of polyester containing ethylene oxide group or isocyanate group; The number average molecular weight of the polymer containing ethylene oxide group or isocyanate group is 1000-10000 Da.

3. The battery binder according to claim 2, characterized in that: The first type of liquid rubber includes one or more of nitrile rubber, styrene-butadiene rubber, polybutadiene rubber, polyurethane rubber, and polysulfide rubber containing terminal hydroxyl groups, amino groups, or mercapto groups; And / or, the second type of liquid rubber includes one or more of nitrile rubber, styrene-butadiene rubber, polybutadiene rubber and polyurethane rubber containing ethylene oxide groups or isocyanate groups.

4. The battery binder according to claim 1, characterized in that: The mass ratio of the polymer containing hydroxyl, amino or mercapto groups to the polymer containing oxirane or isocyanate groups is (5-95): (5-95).

5. Use of the battery binder according to any one of claims 1 to 4 in a battery; the battery is a sulfide solid-state lithium battery.

6. A solid-state lithium battery, characterized in that: Including positive electrode sheet, negative electrode sheet, and sulfide electrolyte membrane; The positive electrode sheet comprises a positive electrode active material, a conductive agent, a sulfide electrolyte and a binder according to any one of claims 1 to 4; And / or, the negative electrode plate comprises a negative electrode active material, a conductive agent, a sulfide electrolyte and the binder according to any one of claims 1 to 4; And / or, the sulfide electrolyte membrane comprises a sulfide electrolyte and the binder according to any one of claims 1 to 4.

7. The solid-state lithium battery according to claim 6, characterized in that: The positive electrode active material includes one or more of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium iron sulfate and ternary positive electrode materials; and / or, the negative electrode active material comprises one or more of metallic lithium, lithium alloy, hard carbon, graphite, molybdenum disulfide, lithium titanate, graphene, silicon dioxide, antimony oxide and silicon monomer; and / or, the conductive agent comprises one or more of carbon nanotubes, carbon black, graphite, graphene, hard carbon and soft carbon; And / or, the sulfide electrolyte includes Li2S, P2S5, Li3PS4, Li7P3S 11 、Li6PS5Cl、Li 9+x-y M x P 3-x S 12-y N y One or more of, wherein 0≤x≤2, 0≤y≤1, M includes one or more of Si, Ge, Sn, and Pb, and N includes one or more of F, Cl, Br, and I.

8. The solid-state lithium battery according to claim 7, characterized in that: The mass ratio of the positive electrode active material, the conductive agent, the sulfide electrolyte and the binder in the positive electrode sheet is (80-98): (0.1-5): (1-15): (0.1-5); And / or, the mass ratio of the negative electrode active material, the conductive agent, the sulfide electrolyte and the binder in the negative electrode plate is (85-100): (0-5): (0-15): (0-5); And / or, the mass ratio of the sulfide electrolyte to the binder in the sulfide electrolyte membrane is (95-99):(1-5).

9. The solid-state lithium battery according to claim 7, characterized in that: The sulfide electrolyte includes a mixture of Li2S and P2S5, and the molar ratio of Li2S to P2S5 is (70-80): (30-20).

10. The solid-state lithium battery according to claim 7, characterized in that: The positive electrode sheet, negative electrode sheet and sulfide electrolyte membrane of the solid-state lithium battery are all prepared by a wet or dry process.

Citation Information

Patent Citations

  • Sulfide solid electrolyte membrane, preparation method thereof and all-solid-state battery

    CN117747926A

  • Method for preparing solid-state battery electrode and solid-state electrolyte membrane

    CN117895090A

  • Binder composition, battery cell, preparation method of battery cell and all-solid-state battery

    CN115528248A

  • Dry electrode binder, negative electrode dry powder mixture and application thereof

    CN116314792A

  • Binder for all-solid-state battery, positive electrode for all-solid-state battery, and all-solid-state battery comprising same

    CN118946988A

Cited By

  • Solid-state battery binder, preparation method and application thereof, composite electrolyte membrane and solid-state battery composite positive electrode

    CN120290124A

  • An all-solid-state sulfide electrolyte membrane, a preparation method therefor, and use thereof

    CN122599510A